Lacustrine, fluvial and slope deposits in the wetland shore area in Serteya, Western Russia - Kittel, Piotr; Mazurkevich, Andrey; Alexandrovskiy, Alexander; Dolbunova, Ekaterina; Krupski, Mateusz; Szmańda, Jacek; Stachowicz-Rybka, Renata; Cywa, Katarzyna; Mroczkowska, Agnieszka; Okupny, Daniel (Acta Geographica Lodziensia, 2020)
The article presents the results of a study on sediment deposition processes in the palaeolake shore zone, at the multilayered Serteya II archaeological site in Western Russia. In recent years, geomorphological, palaeopedological and palaeoecological research was undertaken in strict cooperation with archaeological fieldwork. The Serteya II site occupies a substantial area of a kame terrace and biogenic plain within a palaeolake basin. From an archaeological point of view, the site is represented by few Mesolithic artefacts, but mostly by remnants of hunter–gatherer–fisher communities attributed in the Russian scientific tradition to the Neolithic period and dated from 6300 BC to 2000 BC. Later, the area was used by people in the Bronze Age, Early Iron Age and Early Middle Ages. The integration of archaeological and multidisciplinary palaeoenvironmental research allowed the natural and human induced deposition of mineral-organic and minerogenic sediments to be reconstructed, as well as the development of structures in the lake shore zone. The changes from lacustrine to fluvial system were documented and the human impact is recorded mostly in the acceleration of slope processes.